1999
DOI: 10.1017/s0022149x99000347
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host weight, sex and reproductive status on helminth parasites of the wild rabbit, Oryctolagus cuniculus, in Navarra, Spain

Abstract: A study was carried out in Navarra (northern Spain) on the influence of the weight, sex and reproductive status (lactant, pregnant or lactant + pregnant females and testicular weight for males) of the wild rabbit (Oryctolagus cuniculus) on two cestodes species: Andrya cuniculi and Mosgovoyia ctenoides and four intestinal nematodes: Graphidium strigosum, Trichostrongylus retortaeformis, Nematodiroides zembrae and Dermatoxys hispaniensis. A significantly higher prevalence of A. cuniculi was detected in lactant +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The higher mean intensity of G. strigosum in 2003 is in accordance with the concept of parasite load increasing with age (see Wilson et al , 2001), as also verified for this nematode by Boag & Kolb (1989) in Scotland, and Dunsmore (1966) in Australia. It is thereby suggested that either the wild rabbit does not acquire resistance to infection with increasing age, as also suggested by Molina et al (1999), or that G. strigosum does not respond to host immunity (Lello et al , 2004). Apart from host density and age, according to Dunsmore (1966) and Allan et al (1999), suitable conditions of humidity and temperature could favour these higher values of G. strigosum .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The higher mean intensity of G. strigosum in 2003 is in accordance with the concept of parasite load increasing with age (see Wilson et al , 2001), as also verified for this nematode by Boag & Kolb (1989) in Scotland, and Dunsmore (1966) in Australia. It is thereby suggested that either the wild rabbit does not acquire resistance to infection with increasing age, as also suggested by Molina et al (1999), or that G. strigosum does not respond to host immunity (Lello et al , 2004). Apart from host density and age, according to Dunsmore (1966) and Allan et al (1999), suitable conditions of humidity and temperature could favour these higher values of G. strigosum .…”
Section: Discussionmentioning
confidence: 86%
“…In the Iberian Peninsula, the interpretation of wild rabbit helmithfaunal data in view of ecological and host parameters has been attempted in studies referring to several Spanish regions (e.g. Blasco et al , 1996; Molina et al , 1999), whereas the scarce studies on the helminth parasites of Portuguese wild rabbits are merely descriptive (Carvalho-Varela, 1967; Maia et al , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits in Tenerife have fewer species of parasites than rabbits found in the Iberian Peninsula from where the wild rabbit stocks of the Canary Islands originated. Sixteen helminth species have been reported in the Iberian wild rabbit (Cordero del Campillo et al, 1994;Blasco et al, 1996;Molina et al, 1998Molina et al, , 1999) and this appears to be the richest helminth fauna found in this host in Europe (Blasco et al, 1996). Only a small number of these species were introduced in Tenerife despite the similarities in the flora and fauna of several island zones within the Mediterranean region (Juan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence in the infestation of females could be due to the weakening of the organism as a result of the physiological stress associated with the pregnancies and births. Confirmation of this hypothesis is found in the work of Molina et al (1999) who have established a significantly higher prevalence of the tapeworm Andrya cuniculi in lactating and pregnant wild rabbits compared with non-breeding females.…”
Section: Discussionmentioning
confidence: 67%